Od prevajanja Moliera in Metastasia do uprizarjanja Micke in Matička - Vidmar, Luka (Jezik in slovstvo, 2020)
The article re-examines the formation of Slovenian secular drama and theatre. In 1669 or 1670, Fran Krsto Frankopan started to translate Moliere's comedy George Dandin, and probably around 1775, Jurij Japelj started to translate Metastasio's libretto Artaserse. The first secular play, entitled Opereta, was published by Anton Feliks Dev in 1780. After 1781, Anton Tomaž Linhart and Žiga Zois began to translate Italian arias, and these Slovenian songs were then performed by visiting German and Italian theatre troupes in Ljubljana. The first documented secular theatrical performance was a staging of Linhart's Županova Micka (a translation of Richter's comedy Die Feldmühle) in 1789 in Ljubljana. In 1790, Linhart's Matiček se ženi (an adaptation of Beaumarchais's comedy La Folle Journée ou le Mariage de Figaro) was published, but obviously not performed. After 1803, when Kopitar's Tinček Petelinček (an adaptation of Kotzebue's play Der Hahnenschlag) was staged in Ljubljana, the tradition of Slovenian theatre - despite many new original and translated plays - only continued in 1848.
Keywords: comedy; Dev, Anton Feliks; komedija; Kopitar, Jernej; Linhart, Anton Tomaž; opera; Slovenian literature; Slovenian secular drama; Slovenian secular theatre; slovenska književnost; slovenska posvetna dramatika; slovensko posvetno gledališče; Zois, Žiga